STRATEGI PENDIDIKAN AGAMA DAN MORAL BANGSA - juita, JUITA (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2016)
Abstract: Religious education and moral education got a reasonable place in the national education. Religious and moral education cannot be separated from efforts to instill the value of religion in the learners’ soul. In Islam, moral is a translation of the word character. Moral actions are all kinds of actions intended for someone else. The causes of deviant behaviors among the people because of the looseness of the handle to religion, the lack of effective moral development undertaken by households, schools and communities, the swift currents and the secularistic materialist culture. Kata Kunci: Strategi Pendidikan Agama dan Moral Bangsa